Smart Travelling or the Impact of IT in Tourism - TUDOR, Irina Valentina; POPÎRLAN, Cristina; MITUCĂ, Mircea Ovidiu (Journal of Environmental Management and Tourism; Vol 11 No 4 (2020): JEMT Volume XI Issue 4(44) Summer 2020DO - 10.14505//jemt.v11.4(44).24, 2020)
In this modern and blooming age of technology, tourism along with many other aspects of life are highly impacted by IT industry, especially the social media aspect, where everything is judged and interpreted. It is way simpler nowadays to find reviews online, with pictures included, about everything tourism-related such as places, museums, hotels, restaurants, even the locals. The impact of online information and personal opinions of people about destinations can be very influencing for different types of possible tourists in choosing their vacation or week-end getaway especially now in the growing age of social media, where users share every aspect of their lives, travelling included. We take a look at the various ramifications that computer science has over tourism in general and how it can be of use to the traveler of the 21st century via its many ways of digital interconnection.